2019
DOI: 10.1186/s13052-019-0609-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the predicting factors of recurrent wheezing in infants

Abstract: BackgroundClinically, asthma in children under 5 years old is under estimated because lack of diagnostic criteria. The current study was, therefore, designed to identify the predicting factors for recurrent wheezing in infants.MethodsOne hundred forty-five infants under 3-year old hospitalized with respiratory diseases were enrolled into this study. Patients were followed up for one-year period after being discharged from the hospital and were, then, divided into recurrent wheezing group and non-recurrent whee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Previously, in the same cohort, we have shown that preschool wheezers that develop asthma were hospitalized more often and for more extended periods during their first year after inclusion, indicating more severe symptoms than preschool wheezers that do not develop asthma 6 . This is in line with previous studies that showed higher EDN levels in children with more severe asthma symptoms and where infants hospitalized with recurrent wheezing showed higher EDN levels than infants hospitalized with nonrecurrent wheezing 7 . In adults, higher EDN levels have been associated with current asthma, poor asthma control and asthma treatment during the last year 8 .…”
Section: Figuresupporting
confidence: 92%
“…Previously, in the same cohort, we have shown that preschool wheezers that develop asthma were hospitalized more often and for more extended periods during their first year after inclusion, indicating more severe symptoms than preschool wheezers that do not develop asthma 6 . This is in line with previous studies that showed higher EDN levels in children with more severe asthma symptoms and where infants hospitalized with recurrent wheezing showed higher EDN levels than infants hospitalized with nonrecurrent wheezing 7 . In adults, higher EDN levels have been associated with current asthma, poor asthma control and asthma treatment during the last year 8 .…”
Section: Figuresupporting
confidence: 92%
“…However, how eosinophils modulate adaptive immune responses during bacterial respiratory infections remains not fully understood [ 48 ]. Intriguingly, there is a correlation between respiratory infections and increasing risk of asthma and allergies [ 49 , 50 , 51 , 52 , 53 , 54 ], suggesting that eosinophils might be involved in the immune responses to these infections, and infection-induced dysregulation may contribute to this hyper-responsiveness. However, if the role(s) of eosinophils in the immune response to infection involves complex interactions and communication with multiple other immune cells, it/they might be difficult to detect and/or study in crude models of human pathogens infecting mice.…”
Section: Introductionmentioning
confidence: 99%
“…18 RSV infection prevalence, eosinophil percentage, and serum eosinophil-derived neurotoxin levels are the predominant risk factors of wheezing and could therefore be used to predict recurrent wheezing in infants. 1 The risk factors for developing asthma by 6 years of age in children hospitalized for wheezing before 2 years of age are eosinophils in the blood, atopic dermatitis, elevated serum IgE levels, and wheezing onset in early life. It has been suggested that the defining factor of childhood asthma is atopy.…”
Section: Discussionmentioning
confidence: 99%
“…About half of children experience at least one wheeze before school age, and some of the infants with acute bronchiolitis can develop into recurrent wheezing. 1 Viral infection is the most common cause of wheezing in infants and young children, with human respiratory syncytial virus (RSV) being the most common cause. 2,3 RSV infection can cause irreversible lung damage and increase the incidence of chronic lung disease in adulthood.…”
Section: Introductionmentioning
confidence: 99%